The radiation tolerance of a low voltage LDO developed for the CMS HGCAL on-detector electronics system. (1st March 2022) - Irshad, A.; Ceard, L.; ,
Abstract: The CMS detector will undergo the replacement of its current endcap calorimeter by a new high granularity calorimeter (HGCAL). The new HGCAL will need to withstand much higher radiation levels than the present endcaps. This poses tight requirements on the front-end electronics, including the powering chain. As part of this chain, a low-dropout linear regulator (LDO) has been designed and prototyped for post-regulation for HGCAL, providing extremely low noise and stable power to the analog front-end. We present results from tests of the LDO, including from a detailed irradiation campaign.